LECTURER RESEARCH PERFORMANCE: RESEARCH MOTIVATION, RESEARCH CULTURE AND LECTURER SATISFACTION - ASMIRIN NOOR; ABDUL RAHMAT; SHENNA ZENITHA AFDHALLY, S E (International Journal of Innovations in Engineering Research and Technology, 2021)
This study observes research motivation, research culture on lecturer satisfaction and the resulting performance. The sample of this research is the lecturers who are members of the Lecturers Association of the Republic of Indonesia, East Java, totaling 199 people. The results of the study found: Research motivation has no significant effect on research satisfaction, Research motivation has a significant effect on research performance, Research culture has a significant effect on satisfaction, Research culture has a significant effect on performance and research satisfaction has a significant effect on the researching performance of lecturers.